271 ONTOGENY OF VASCULAR ENDOTHELIAL GROWTH FACTOR, INSULIN-LIKE GROWTH FACTOR-I, AND GROWTH HORMONE IN THE RAT VITREOUS FLUID, RETINAL HOMOGENATES, AND SYSTEMIC CIRCULATION: RELATIONSHIP TO PHYSICAL GROWTH AND RETINAL DEVELOPMENT. (10th December 2015) - Gharraee, Z.; Beharry, K. D.A.; Hasan, J.; Waltzman, J.; Nageotte, S.; Modanlou, H. D.
Abstract : Vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF)-I, and growth hormone (GH) are important regulators of physical growth and have been shown to play key roles in retinal angiogenesis and development. In premature infants, low serum IGF-I and high GH levels in the early postnatal period were reported to be associated with severe retinopathy of prematurity (ROP). We examined the ontogenic profile of VEGF, IGF-I and GH in rat vitreous fluid, retinal homogenates and systemic circulation from birth to 21 days postnatal age (weaning, P21). Sprague Dawley rats (litter size =15 pups) were sacrificed at P0, P7, P14 and P21 (3 litters/group). At sacrifice, the pups were weighed and measured for linear growth (nose to tail length). Vitreous fluid, retinal homogenates, and serum were analyzed for VEGF, IGF-I and GH by enzyme immunoassay. VEGF levels were 10-fold higher in the vitreous (pg/mL) than serum (pg/mL) at all stages of development. Vitreous and serum VEGF levels progressively declined at P7, P14 and P21 (p≤0.05 to p≤0.001) compared to term, however in the retinal homogenates, VEGF levels (pg/mg protein) increased with the highest concentration at P21 (p≤0.05 vs term). Vitreous IGF-I levels were decreased at P7 through P14 (p≤0.05) compared to term. Vitreous GH levels were 10-fold lower than serum levels and were decreased at P14 and P21 (p≤0.001) compared to P7. Despite a trend for increasing IGF-I and decreasing GH in retinal homogenates, no appreciable changes were detected with advancing postnatal age. Similarly, serum IGF-I levels increased with postnatal age (P14 and P21: p≤0.05 vs term), whereas serum GH levels were decreased at P7 (p≤0.05), P14 (p≤0.01), and P21 (p≤0.01) compared to term. In rats, retinal development occurs postnatally by P14. Our data demonstrate that during normal retinal development, VEGF, IGF-I and GH decrease in the vitreous; and VEGF and IGF-I increase, while GH decreases in the retinal homogenates. A quite different ontogenic pattern is noted in the systemic circulation. VEGF and GH decrease, while IGF-I increases with advancing physical growth. We therefore conclude that any future therapy for ROP should consider changes occurring in the eye rather than the systemic compartment.